2004
DOI: 10.1042/cs20030238
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of cellular FLICE-inhibitory protein (FLIP) in gastric adenocarcinoma

Abstract: The aim of the present study was to investigate the prevalence of c-FLIP [cellular FLICE-inhibitory protein, where FLICE is Fas-associated death domain (FADD)-like interleukin-1beta-converting enzyme] expression in gastric adenocarcinoma and its possible implications for the progression of the cancer. Expression of c-FLIP in 48 gastric adenocarcinomas and their normal counterparts was analysed by reverse transcriptase PCR, Western blotting and immunohistochemistry. In situ cell apoptosis was detected by TUNEL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 38 publications
3
65
1
Order By: Relevance
“…FLIP has been found to be overexpressed in many human cancers (Ryu et al, 2001;Zhou et al, 2004;Valnet-Rabier et al, 2005), and has emerged through our work and that of others, as a potential anti-cancer drug target (Hyer et al, 2005;Wilson et al, 2007). Furthermore, XIAP has been found to be overexpressed in several cancers, and small molecule and antisense approaches to target XIAP are in development (Hu et al, 2003;LaCasse et al, 2006).…”
Section: Discussionmentioning
confidence: 72%
“…FLIP has been found to be overexpressed in many human cancers (Ryu et al, 2001;Zhou et al, 2004;Valnet-Rabier et al, 2005), and has emerged through our work and that of others, as a potential anti-cancer drug target (Hyer et al, 2005;Wilson et al, 2007). Furthermore, XIAP has been found to be overexpressed in several cancers, and small molecule and antisense approaches to target XIAP are in development (Hu et al, 2003;LaCasse et al, 2006).…”
Section: Discussionmentioning
confidence: 72%
“…In both studies, increased c-FLIP S protein expression correlated with decreased caspase-8 processing at the Fas-mediated death-inducing signaling complex (44,45). Other studies indicate a role for elevated c-FLIP S in the survival of various tumor cells, including human gastric cancers (55,56) and cells from patients with myelodysplastic syndrome (57). We propose an alternative mechanism of generating p27FLIP by further cleavage of p43FLIP.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, clinical studies have demonstrated significantly elevated c-FLIP expression in colorectal and gastric tumours (Ryu et al, 2001;Zhou et al, 2004), suggesting that c-FLIP may be a relevant clinical target not only in CRC but also in gastric cancer, where 5-FU-based chemotherapy regimens are also used. Moreover, our data suggest that c-FT therapeutic strategies may be effective against colorectal tumours irrespective of p53 mutational status.…”
Section: Discussionmentioning
confidence: 99%